Incorporating Prey Refuge in a Prey-Predator Model with Beddington-DeAngelis Type Functional Response: A Comparative Study on Intra-Specific Competition - Molla, Hafizul; Rahman, Md. Sabiar; Sarwardi, Sahabuddin (Discontinuity, Nonlinearity, and Complexity, 2026)
The present study deals with a prey-predator system with prey refuge depending on both species with the Beddington-DeAngelis response function. We propose a mathematical model for predator-prey interactions, allowing prey refuge in the absence of intra-specific competition and in the presence of intra-specific competition among the predators. We have analyzed the models in terms of boundedness, persistence, existence of equilibria and their stability and Hopf bifurcation. Existence of paradox of enrichments are examined well in both the cases. The analytical findings of this study are substantially validated by sufficient numerical simulations. The ecological implications of the obtained results are discussed as well.